Pelatihan pertolongan pertama pada kasus patah tulang di lingkungan Sekolah Menengah Pertama Negeri 2 Kota Lubuklinggau - Wijaya, Sapondra; Susmini, Susmini; Soewito, Bambang; Wibowo, Wahyu Dwi Ari; Salsabilla, Naura Yuri; Oktapiani, Putri Ayu; Putri, Cindy Arina (Nur Science Institute, 2024)
Accidents can happen unexpectedly and can happen anywhere, such as at home, on the street, including at school. One of the most common cases is a fracture. Knowledge of initial aid for fracture cases from teachers, employees, and even students is an essential point in preventing the worsening of the victim's condition before being taken to a health facility. It is necessary to increase knowledge of prevention and first aid in fracture cases at school by students and UKS coaches. The method of community service activities is education and training on first aid in fracture cases in schools, targeting UKS cadres. After the community service activities, the participant's knowledge about the first handling of fracture cases increased. The implication is that when there is a fracture victim, first aid measures can be given at the scene without waiting for the medical team to arrive.